2016
DOI: 10.1016/j.jeoa.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting trends in disability in a super-aging society: Adapting the Future Elderly Model to Japan

Abstract: Japan has experienced pronounced population aging, and now has the highest proportion of elderly adults in the world. Yet few projections of Japan’s future demography go beyond estimating population by age and sex to forecast the complex evolution of the health and functioning of the future elderly. This study estimates a new state-transition microsimulation model – the Japanese Future Elderly Model (FEM) – for Japan. We use the model to forecast disability and health for Japan’s future elderly. Our simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…Previous studies have shown that the incidence of urolithiasis has increased steadily since World War II in Japan with a Westernized lifestyle and dietary habits . Another prominent characteristic is that Japan is currently experiencing pronounced population aging, and it now has the highest proportion of older adults in the world . These characteristics might affect the incidence and composition of urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the incidence of urolithiasis has increased steadily since World War II in Japan with a Westernized lifestyle and dietary habits . Another prominent characteristic is that Japan is currently experiencing pronounced population aging, and it now has the highest proportion of older adults in the world . These characteristics might affect the incidence and composition of urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…A potential limitation of this investigation is that the subjects were dentulous and aged between 23 and 45 years. Patients with cancer requiring MR imaging are typically elders (1). However, we consider that this evaluation is effective in older adults and cancer-affected subjects as we were able to evaluate images in a dentulous patient, moving the tongue consciously to cause significant motion artifact.…”
Section: Discussionmentioning
confidence: 99%
“…According to an unprecedented super-aged Japanese society demographic, tongue cancer, salivary gland disease, and temporomandibular joint disease are expected to increase (1). Prevalence of cancer among those aged 50 years and older is expected to increase by 2040 in the Japanese population (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of aging in Japan is currently the highest in the world, and the ≥ 65-year-old population is projected to account for nearly 40% of the total population by the year 2050 (Chen et al 2016). Thus, the prevalence of several diseases, including vertebral compression fracture (VCF), pneumonia, heart failure, and age-related dementia, might increase further (Tsuda 2017;Miyashita and Yamauchi 2018;Shimada et al 2018).…”
Section: Introductionmentioning
confidence: 99%